DUALISM ON TYPE OF LAWSUIT AND PROCEDURE LAW IN THE PERSPECTIVE OF LAND PROCUREMENT/ACQUISITION DISPUTES FOR PUBLIC INTERESTS - Alifin Nurahmana Wanda (Perspektif, 2019)
The existence of the principle as well as the norm that the judge/court must not reject the case (ius curia novit), it turned out to be an interesting discussion in the discourse regarding land procurement/acquisition disputes for public interests, which have been known together that the arrangements regarding the procedure for settlement, land procurement/acquisition disputes for public interests is regulated separately outside the BW and HIR/RIB, namely by law of RI No.2 of 2012. So in a land procurement/acquisition dispute for public interests, in the name of the principle and norm of ius curia novit, is it still possible to file a lawsuit in violation of law through mechanisms and procedures as regulated by BW (material civil) and HIR/RIB (formal civil), and therefore there is no need to submit to the provisions of the Law of RI (UU RI) No. 2 of 2012 or in other wise it means crashing into the norm preference principle namely lex specialis derogat legi generali? Though both of these principles are the same position and degree. To answer that question, each description will be discussed about the concept of the two principles from the viewpoint of legal theory, then later it will be described which concept is more relevant to the benefit and law enforcement based on rational legal arguments, so as to create legal certainty, justice, and legal usefulness in resolving land acquisition disputes in the public interests in Indonesia.